Alfonso de Madrigal and Juan de Segovia: Some Conciliar Common (and Contested) Places. - MANN, JESSE D. (Renaissance & Reformation / Renaissance et Réforme, 2019)
This article offers a preliminary comparison of the thoughts of Alfonso de Madrigal and Juan de Segovia, two important fifteenth-century Spanish academics and authors whom scholars have seen as ideological allies. It identifies several areas of interest common to both writers, and then focuses on their conciliarist views. It argues that while Madrigal and Segovia both asserted several conciliar "common places," often in similar terms, their ecclesiological positions differed in significant ways. Madrigal's "theoretical" conciliarism is contrasted with Segovia's "engaged" conciliarism in order to illuminate the notable differences in their respective careers and influence. The article concludes with a call for closer comparative study of these two wide-ranging thinkers.